FACTORES QUE RESTRINGEN LA COMPETITIVIDAD DE LAS EMPRESAS NACIONALES EN MATERIA TRIBUTARIA - Vega Centeno, Máximo Ugarte (2007)
At the moment the tributary systems should complete economic functions to produce resources for the production of goods and public services, inside the orientation of a short term economic politics of stability. As well we know, in Peru the revenues that the Government in tributary matter are given mainly by the collection from the General Tax to the Sales, Selective Tax to the Consumption, Tax to the External Trade, Tax to the Rent and the Tax to the Financial Transactions. However, it exists in our structure tributary factors that you/they restrict the competitiveness that you/they affect the production and the managerial productivity. In that sense it is required a tributary system with definitions and clear and transparent norms, without bureaucratic barriers that it is flexible and quickly adapted to the changes of the internal and external environment. This system goes by the modernization or reformation of the State that it is a demand of the institutional invigoration of the country.